The effects of emotional intelligence and stress‐related presenteeism on nurses' well‐being. (9th June 2014) - Karimi, Leila; Cheng, Cindy; Bartram, Timothy; Leggat, Sandra G; Sarkeshik, Sara
<x xml:space="preserve">Abstract</x> Emotional intelligence has long been associated with lower levels of stress and enhanced well‐being. This paper contributes empirically by examining the direct and moderating effects of emotional intelligence on the presenteeism and well‐being relationship. A sample of 312 registered nurses who provide home‐based care in an Australian community nursing service were recruited to take part in the study. Results from structural equation modelling revealed that emotional intelligence has direct and moderating effects on well‐being. Stress‐related presenteeism significantly predicted nurses' well‐being. These findings provide further support for the positive effects that emotional intelligence can have on the effective management of job stress and the enhancement of nurse well‐being. We advocate more nursing training on emotional intelligence, and examine the potential benefits of emotional intelligence training and other related HR initiatives.